Cholera Toxins - Chaudhuri, Keya.; Chatterjee, S. N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Vibrio cholerae, the causative organism of the disease Cholera, colonizes the small intestine and produces several different toxins among which the enterotoxin, or more widely known as cholera toxin (CT), happens to be the major virulence determinant that is responsible for the diarrheal syndrome. This book provides for the first time comprehensive and up-to-date information about all the toxins of Vibrio cholerae, their physical and chemical structures, their biosynthesis and its genetic regulation, their physiology, the molecular biology of their interactions with the host as well as their role in the development of an appropriate and effective cholera vaccine. It also offers relevant and necessary background information on the basic biology of the Vibrio cholerae cell and cholera bacteriophages.
An Introduction to Cholera -- Bacterial Toxins: A Brief Overview -- Vibrio cholerae, the Causative Organism -- Endotoxin of Vibrio cholerae: Physical and Chemical Characterization -- Endotoxin of Vibrio cholerae: Genetics of Biosynthesis -- Endotoxin of Vibrio cholerae: Biological Functions -- Cholera Toxin (CT): Structure -- Cholera Toxin (CT): Organization and Function of the Relevant Genetic Elements -- Cholera Toxin (CT): Regulation of the Relevant Virulence Genes -- Cholera Toxin (CT): Secretion by the Vibrios -- Cholera Toxin (CT): Entry and Retrograde Trafficking into the Epithelial Cell -- Cholera Toxin (CT): Immune Response of the Host and Vaccine Production -- Other Toxins of Vibrio cholerae -- Concluding Notes.
Keywords: Medicine; Medical microbiology; Pharmacology; Food -- Biotechnology; Biochemistry; Cell biology; Microbiology; Biomedicine; Medical Microbiology; Microbiology; Food Science; Biochemistry, general; Cell Biology; Pharmacology/Toxicology.; Electronic books